2015
DOI: 10.1063/1.4922301
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between switching to n-type conductivity and structural defects in highly Mg-doped InN

Abstract: The effect of Mg doping on the microstructure of InN epitaxial films in relation to their free-charge carrier properties has been investigated by transmission electron microscopy (TEM) and aberration corrected scanning TEM. We observe a direct correlation between Mg concentration and the formation of stacking faults. The threading dislocation density is found to be independent of Mg concentration. The critical Mg concentration for the on-set of stacking faults formation is determined and found to correlate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In practice for planar growth on sapphire, there is only p-type conduction realized in a doping window 3 × 10 18 to 3 × 10 19 cm –3 , at lower doping the material becomes degenerate n-type due to a dominance of shallow donors . At Mg-doping above 10 20 cm –3 , InN becomes n-type due to an abundance of structural defects (such as stacking faults) creating donors . Because of such defect-related problems in the present InN planar technology with growth on sapphire, InN devices are not well developed.…”
Section: Iii-nitride Nanowire Materials and Devicesmentioning
confidence: 97%
See 1 more Smart Citation
“…In practice for planar growth on sapphire, there is only p-type conduction realized in a doping window 3 × 10 18 to 3 × 10 19 cm –3 , at lower doping the material becomes degenerate n-type due to a dominance of shallow donors . At Mg-doping above 10 20 cm –3 , InN becomes n-type due to an abundance of structural defects (such as stacking faults) creating donors . Because of such defect-related problems in the present InN planar technology with growth on sapphire, InN devices are not well developed.…”
Section: Iii-nitride Nanowire Materials and Devicesmentioning
confidence: 97%
“…447 At Mg-doping above 10 20 cm −3 , InN becomes n-type due to an abundance of structural defects (such as stacking faults) creating donors. 448 Because of such defect-related problems in the present InN planar technology with growth on sapphire, InN devices are not well developed. There is indeed a need for development of high quality bulk InN materials for high quality substrates.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Khromove et al recently identified a strong correlation between the switch to n-type conductivity in highly Mg-doped InN and structural distortion. 31 They observed the formation of stacking faults (SFs) in an InN film with an Mg concentration of 1.8 × 10 20 cm −3 using high-resolution STEM (HRSTEM) (n-type conductivity was observed with a free charge carrier density of 9 × 10 17 cm −3 .) They authors suggested that the stacking faults (SFs) critically increase the concentration of point defects that act as donors in InN.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the conductivity of the Mg-doped InN sample is very important because it is related to its structural characteristics. 31,32 Mg concentration, [Mg], that provides for p-type conductivity in InN has been demonstrated to be in the range 1.0 × 10 18 cm −3 [Mg] 2.9 × 10 19 cm −3 . 33 Mg-doped InN becomes n-type when [Mg] exceeds 2.9 × 10 19 cm −3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation